Do factors related to participation in physical activity change following restrictive bariatric surgery? A qualitative study - Zabatiero, J.; Smith, Anne; Hill, Kylie; Hamdorf, J.; Taylor, S.; Hagger, Martin; Gucciardi, Daniel (Elsevier BV, 2017)
Aims: To explore participants’ ability to participate in physical activity (PA), and barriers and facilitators to PA, at 12 months following restrictive bariatric surgery, and how these differed from participants’ pre-surgery perceptions. Motivators for PA post-surgery were also explored. Methods: Qualitative one-on-one in-depth interviews were conducted pre- and 12 months post-surgery. Data were analysed using inductive thematic analysis. Results: Fourteen adults (12 females), with a mean (range) age of 41.4 years (25.0–56.0), body mass index (BMI) of 31.7 kg/m2 (22.3–48.2), and excess weight loss of 66% (2–127) completed both interviews. Lack of participation in PA during the first 3–6 months post-surgery was a common theme. Although participants reported increased ability to participate in PA, attributing this to a reduction in obesity-related physical barriers to PA, many participants reported that some pre-surgery obesity-related barriers to PA remained at 12 months post-surgery. For most participants, pre-surgery non-obesity related barriers to PA also remained at 12 months post-surgery. Facilitators to PA were consistent pre- and post-surgery. Weight loss and improvement in physical appearance were the most common motivators for PA post-surgery. Conclusions: At 12 months following surgery, many participants reported residual obesity and non-obesity related barriers to PA. These barriers may explain the small, if any, pre- to post-surgery change in PA levels reported by earlier research. Facilitators to PA did not change and post-surgery motivators for PA were mostly esteem-related. These data are relevant to shape interventions aimed at optimising PA in this population.